The impact of liquidity risk on the bank financial performance: the case of the UK commercial banks - FAN, YUJIA (2022)
This study analyses the influence of liquidity risk on bank performance. Return on Assets (ROA) employing the fixed effects model and Return on Equity (ROE) using the random effects model of UK commercial banks. The time period covered by this research is from 2012 to 2021, and panel data from 45 banks of UK commercial banks are used. According to the findings, liquidity risk which is reflected by net loans to total assets (NLTA) has a beneficial effect on bank performance. This finding suggests that the majority of the banks with superior performance also have a greater level of liquidity risk. In addition, the profitability of commercial banks in the UK is affected by variables unique to the banks themselves, such as bank size, bank capital, non-performing loans, and the efficiency of management. GDP growth and inflation, two external macro variables that were addressed in multiple types of research, were shown to have no discernible impact on the operation of UK commercial banks. As a consequence of these findings, it is suggested that banks exercise proper control and management over these factors in order to generate high levels of liquidity, and thus achieve both strong profitability and assure the continued viability of the global banking system. The findings of this research are meant to provide further context to the findings of previous experiments and to provide some recommendations for best practices in bank management relevant to this field.